Living and Dying in a Virtual World Digital Kinships, Nostalgia, and Mourning in Second Life - Gibson, Margaret (Palgrave Macmillan Memory Studies, 2018)
This book takes readers into stories of love, loss, grief and mourning and reveals the emotional attachments and digital kinships of the virtual 3D social world of Second Life. At fourteen years old, Second Life can no longer be perceived as the young, cutting-edge environment it once was, and yet it endures as a place of belonging, fun, role-play and social experimentation. In this volume, the authors argue that far from facing an impending death, Second Life has undergone a transition to maturity and holds a new type of significance. As people increasingly explore and co-create a sense of self and ways of belonging through avatars and computer screens, the question of where and how people live and die becomes increasingly more important to understand. This book shows how a virtual world can change lives and create forms of memory, nostalgia and mourning for both real and avatar based lives.